Eco driving - Klimska, Agnieszka; Klimski, Marcin (Studia Ecologiae et Bioethicae, 2009)
The article touches on the question of eco-driving – a conception that offers a turn of the style of driving into more economical and more favorable to the environment. There have been shown the assumptions of eco-driving which provide a reduction in fuel consumption and, thanks to that, a saving of money and the environment’s components. The increase of a driving culture thanks to eco-driving may become one of the methods of activization the informal environmental education.